2012
DOI: 10.7314/apjcp.2012.13.11.5903
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effects of Exemestane and Aspirin on MCF-7 Human Breast Cancer Cells

Abstract: Objective: The purpose of this study is to investigate the combined effects of exemestane and aspirin on MCF-7 human breast cancer cells. Methods: Antiproliferative effects of exemestane and aspirin, alone and in combination, on growth of MCF-7 human breast cancer cells were assessed using the MTT assay. Synergistic interaction between the two drugs was evaluated in vitro using the combination index (CI) method. The cell cycle distribution was analyzed by flow cytometry and Western blotting was used to investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 45 publications
0
11
1
Order By: Relevance
“…Therefore, the difference between aspirin and diclofenac against the fibroblast cell growth may be related to the concentration of the drug that deposited in fibroblast cells. The results of NSAIDs on the mammary cell growth do not agree the previous reports that showed aspirin induced breast cancer apoptosis in presence of over-expression of Bcl-2 gene (Choi et al, 2013; Hu et al, 2012). Therefore, NSAIDs inhibit the growth of breast cell cancer in specific experimental models, otherwise, their cytotoxic effect is missed.…”
Section: Discussioncontrasting
confidence: 95%
“…Therefore, the difference between aspirin and diclofenac against the fibroblast cell growth may be related to the concentration of the drug that deposited in fibroblast cells. The results of NSAIDs on the mammary cell growth do not agree the previous reports that showed aspirin induced breast cancer apoptosis in presence of over-expression of Bcl-2 gene (Choi et al, 2013; Hu et al, 2012). Therefore, NSAIDs inhibit the growth of breast cell cancer in specific experimental models, otherwise, their cytotoxic effect is missed.…”
Section: Discussioncontrasting
confidence: 95%
“…There is increasing interest in cancer prevention and in the drugs that, used in low doses, either alone or in combination, which have different modes of action and low toxicity, act as chemopreventive agents (47). Therefore, the present study investigated other molecules, which are used for the treatment of well-known pathological diseases and have effects on cancer cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Therapeutic strategies using a combination of drugs in order to enhance the efficacy of cancer treatment have recently garnered attention. The drugs may act together synergistically to inhibit tumor progression through the regulation of various signaling pathways, or reverse the cancer-specific upregulated cell proliferation or evasion of apoptosis (23). The present study chose to evaluate combinations of statin drugs, based upon previously reported cytotoxic experience in breast cancer cell lines (24,25).…”
Section: Introductionmentioning
confidence: 99%